Analisis Aspek Hukum Dalam Penerapan Sanksi Administratif Pajak Penghasilan Di Indonesia - Adhyaksa Muhammad Ilham Soekotjo (Journal of Innovative and Creativity, 2026)
This study aims to analyze the legal aspects of the application of administrative sanctions for income tax (PPh) in Indonesia, particularly in relation to legal certainty, proportionality of sanctions, and the authority of the tax authorities in imposing administrative tax measures. The research method used is normative legal research with a legislative approach, a case approach, and a conceptual approach. The results of the study show that although the legal basis for administrative sanctions for income tax is clearly regulated in the General Provisions and Tax Procedures Law (KUP Law), there are several legal issues such as multiple interpretations of articles, inconsistencies in implementing regulations, and the potential for arbitrariness in tax audits and assessments. This study concludes that legal certainty and the protection of taxpayer rights still need to be strengthened through improvements in regulations and standard procedures for tax law enforcement.